ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PERINGKAT OBLIGASI PADA LEMBAGA KEUANGAN BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Irma Febriani; Hari Susanta Nugraha; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2013)
This research aims to analyze the factors that affect bond ratings on banks listed on the Indonesia Stock Exchange. Where the suspected factors that affect the bond rating are firm growth, firm size (size), the company's liquidity, secure, maturity, and the auditor's reputation. The study is included in the explanatory type. The sampling technique used purposive sampling techniques, the sample amounted to 10 banks listed on the Indonesia Stock Exchange. The method of analysis used in this study is the factor analysis and logistic regression analysis. The factor analysis result shows that growth, size, liquidity, and auditor reputation are factors that affect on bond ratings. Secure and maturity are not included in these factors due to the value of MSA are not qualified testing. The logistic regression result shows that size affect on bond ratings. It means that size can make the bank bond ratings turn into good or bad. While the growth, liquidity, and auditor reputation has no effect to bank bond ratings. It means that the level of these variables have no impact on banks bond ratings.